2018
DOI: 10.4025/jphyeduc.v30i1.3002
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de parâmetros metabólicos em crianças e adolescentes com e sem resistência à insulina

Abstract: O objetivo do estudo foi comparar o comportamento de parâmetros metabólicos, pressão arterial e indicadores de obesidade  em crianças e adolescentes com e sem resistência à insulina. Participaram do estudo 60 crianças e adolescentes com excesso de peso (6 a 18 anos) que foram submetidos a medidas antropométricas de massa corporal (MC), estatura e circunferência da cintura (CC), pressão arterial (PA), bioimpedância [gordura relativa (%G) e absoluta (GC)] e coleta sanguínea para determinação das concentrações de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…A study conducted by Peplies et al (31) with children aged 3 to 10 years reported that body fat and lesser time spent on active activities during the day were positively associated with insulin resistance. In this sense, the relationship of these markers is in agreement with the literature, which indicates that the consumption of certain foods, especially those rich in sugar and fats, and obesity are risk factors for the development of insulin resistance, consequently associated with changes in metabolic parameters, LDL-c, total cholesterol and triglycerides in children (22,23). Furthermore, the presence of FTO gene polymorphism leads to alterations in blood glucose and insulin, increase in body fat, as well as greater consumption of processed foods that corroborate cardiometabolic alterations (16,24,42).…”
Section: Discussionsupporting
confidence: 90%
“…A study conducted by Peplies et al (31) with children aged 3 to 10 years reported that body fat and lesser time spent on active activities during the day were positively associated with insulin resistance. In this sense, the relationship of these markers is in agreement with the literature, which indicates that the consumption of certain foods, especially those rich in sugar and fats, and obesity are risk factors for the development of insulin resistance, consequently associated with changes in metabolic parameters, LDL-c, total cholesterol and triglycerides in children (22,23). Furthermore, the presence of FTO gene polymorphism leads to alterations in blood glucose and insulin, increase in body fat, as well as greater consumption of processed foods that corroborate cardiometabolic alterations (16,24,42).…”
Section: Discussionsupporting
confidence: 90%